Shadow economy and entrepreneurial entry - Saul Estrin; Tomasz Mickiewicz (Institute for the Study of Labor (IZA), 2010)
We analyze theoretically and empirically the impact of the shadow economy on entrepreneurial entry, utilising 1998-2005 individual-level Global Entrepreneurship Monitor data merged with macro level variables. A simple correlation coefficient suggests a positive linear link between the size of the shadow economy and entrepreneurial entry. However, this masks more complex relationships. With appropriate controls and instrumenting for potential endogeneity where required, the impact of the shadow economy on entry is found to be negative, based on a linear specification. Moreover, there is also evidence of nonlinearity: entrepreneurial entry is least likely when the shadow economy is of medium size. We attribute the negative effects of shadow economy on entry to perceived strong competition faced by new entrants when the shadow economy is widespread. At the individual level, an extensive shadow economy has a more negative impact on respondents who are risk averse. In addition, in the economies where property rights are strong, the negative impact of the shadow economy is weaker.
Keywords: O17; D2; L26; P14; 330; shadow economy; entrepreneurship; Unternehmer; Unternehmensgründung; Markteintritt; Schattenwirtschaft; Eigentumsrecht; Schätzung; Welt